2021
DOI: 10.1021/acs.jmedchem.1c01207
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Potent and Selective 2-(Benzylthio)pyrimidine-based DCN1-UBC12 Inhibitors for Anticardiac Fibrotic Effects

Abstract: DCN1, a co-E3 ligase, interacts with UBC12 and activates cullin–RING ligases (CRLs) by catalyzing cullin neddylation. Although DCN1 has been recognized as an important therapeutic target for human diseases, its role in the cardiovascular area remains unknown. Here, we first found that DCN1 was upregulated in isolated cardiac fibroblasts (CFs) treated by angiotensin (Ang) II and in mouse hearts after pressure overload. Then, structure-based optimizations for DCN1-UBC12 inhibitors were performed based on our pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…Moreover, given that the antioxidant transcription factor NRF2 is a typical substrate of cullin3 10 , DCN1 inhibitors probably play vital role for the treatment of diseases related to over-production of ROS. In particular, the recent findings disclosed that DCN1 inhibitors possessed evident potency on reducing acetaminophen-induced liver damage and AngⅡ-induced cardiac fibrosis, connected with the inhibition of cullin3 neddylation and its substrate NRF2 activation 142 , 145 . Besides, considering that neddylation inhibition well sensitize chemo-/radio-resistant cancer cells 159 , 167 , 172 , DCN1 inhibitors can be used to investigate their potency on relieving resistance in the future.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, given that the antioxidant transcription factor NRF2 is a typical substrate of cullin3 10 , DCN1 inhibitors probably play vital role for the treatment of diseases related to over-production of ROS. In particular, the recent findings disclosed that DCN1 inhibitors possessed evident potency on reducing acetaminophen-induced liver damage and AngⅡ-induced cardiac fibrosis, connected with the inhibition of cullin3 neddylation and its substrate NRF2 activation 142 , 145 . Besides, considering that neddylation inhibition well sensitize chemo-/radio-resistant cancer cells 159 , 167 , 172 , DCN1 inhibitors can be used to investigate their potency on relieving resistance in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Our group observed that DCN1 protein was obviously upregulated in isolated cardiac fibroblasts treated by Angiotensin (Ang) II and in mouse hearts after pressure overload. However, inhibition of DCN1 effectively reversed Ang II-induced cardiac fibroblast activation, which was associated with the inhibition of cullin 3 neddylation and the accumulation of its substrate protein NRF2 145 . Besides, we also found that treated with DCN1 inhibitor could potentially relieved liver fibrosis in CCl4-induced mouse model 141 .…”
Section: Role Of Neddylation On Fibrotic Diseasesmentioning
confidence: 97%
See 2 more Smart Citations
“…Its related pathways include Class I MHC‐mediated antigen processing and presentation and regulation of activated PAK‐2p34 by proteasome‐mediated degradation. DCN1 is a co‐E3 ligase that interacts with UBC12, and inhibitors of DCN1–UBC12 interaction are effective in alleviating myocardial fibrosis, 25 which is known to be associated with the prognosis of DCM. 26 The expression of UBC12 in chronic VMC samples was significantly different from normal samples, hence the indispensable role of UBC12 in improving the prognosis of DCM.…”
Section: Discussionmentioning
confidence: 99%